Awareness in contextual cuing with extended and concurrent explicit tests - Smyth, Andrea C.; Shanks, David R. (Memory & cognition, 2008)
The term contextual cuing refers to improved visual search performance with repeated exposure to a configuration of objects. Participants use predictive cues-derived from learned associations between target locations and the spatial arrangement of the surrounding distractors in a configuration-to efficiently guide search behavior. Researchers have claimed that contextual cuing can occur implicitly. The present experiments examined two explicit measures-generation and recognition. In Experiment 1, we found that contextual cuing information was consciously retrievable when the number of trials used in a generation test was increased, and the results also suggested that the shorter tests that were used previously were not statistically powerful enough to detect a true awareness effect. In Experiment 2, concurrent implicit and explicit (generation and recognition) tests were employed. At a group level, learning did not precede awareness. Although contextual cuing was evident in participants who were selected post hoc as having no explicit awareness, and for specific configurations that did not support awareness, we argue that awareness may nevertheless be a necessary concomitant of contextual cuing. These results demonstrate that contextual cuing knowledge is accessible to awareness.